Epidemiology and incidence of HPV‐related cancers of the head and neck. Issue 6 (23rd September 2021) - Roman, Benjamin R.; Aragones, Abraham
Abstract: Globally, 4.5% of cancers are due to the human papillomavirus (HPV). In the United States, 80 million people are infected with HPV, and the incidence of HPV oropharyngeal cancer has surpassed HPV cervical cancer. The highest burden of oropharyngeal cancer is seen in middle‐aged and increasingly older White men. HPV vaccination promises to change the epidemiology of this disease, but HPV vaccination rates remain too low today to reduce disease transmission.